2013
DOI: 10.1016/j.cca.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Foam cells in atherosclerosis

Abstract: Atherosclerosis is a chronic disease characterized by the deposition of excessive cholesterol in the arterial intima. Macrophage foam cells play a critical role in the occurrence and development of atherosclerosis. The generation of these cells is associated with imbalance of cholesterol influx, esterification and efflux. CD36 and scavenger receptor class A (SR-A) are mainly responsible for uptake of lipoprotein-derived cholesterol by macrophages. Acyl coenzyme A:cholesterol acyltransferase-1 (ACAT1) and neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
506
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 642 publications
(523 citation statements)
references
References 81 publications
6
506
0
11
Order By: Relevance
“…Meanwhile, ATP attenuated fat deposition in cardiac epicardium and reduced foam cells in thoracic aorta. It is well known that foam cell promotes the formation of fatty streak in blood vessels that is an early marker of atherosclerosis (Botham et al 2007;Yu et al 2013). It is generally accepted that total TG levels are an independent predictor for coronary heart diseases (Imke et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ATP attenuated fat deposition in cardiac epicardium and reduced foam cells in thoracic aorta. It is well known that foam cell promotes the formation of fatty streak in blood vessels that is an early marker of atherosclerosis (Botham et al 2007;Yu et al 2013). It is generally accepted that total TG levels are an independent predictor for coronary heart diseases (Imke et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Three types of carriers for cholesterol efflux have so far been identified, ABCA1, ABCG1 and SR-B1. ABCA1 mainly presents to apoA-I, while ABCG1 and SR-B1 present to mature HDL [32] . Recently, Fu et al [33] found that ABCA12 deficiency increased ABCA1 degradation, added to the accumulation of cholesterol in macrophages and the formation of foam cells and damaged the process of macrophage RCT, which resulted in the promotion of AS progression.…”
Section: Effects Of Macrophage Autophagy On Cholesterol Effluxmentioning
confidence: 99%
“…71 In macrophages and VSMCs derived from atherosclerotic plaques, ABCA1 expression and ApoA1-binding capacity is markedly reduced that in turn diminishes ApoA1-mediated cholesterol efflux and promotes lipid deposition. [71][72][73][74] Notably, as mentioned above, ApoA1 could be modified in atherosclerotic plaques through oxidation, nitration, and other mechanisms. This could greatly impair functional properties of intact ApoA1 and even make it dysfunctional.…”
Section: Role Of Modified Apoa1 In Atherosclerosismentioning
confidence: 99%